(untitled) (Journal of Educational Sciences, 2020)
The article summarizes 10 years of innovative work experience of the School of Curators and Advisers (SCA) at Al-Farabi Kazakh National University. Educational activity in higher education has its own characteristics, differs from the school area of activity. It is more professionally oriented, includes the development of common competencies – communication, resilience, stress resistance, creativity, etc. The article reflects the development of new approaches to the educational work of the university. The purpose of the article is to summarize the practical experience of the School of Advisers and Curators at Al-Farabi Kazakh National University, to identify important areas of development of the academic environment through the experience of conducting trainings on educational work, the development of the organizational culture of teachers and educational traditions, strategies and technologies in university education. Great importance in higher education is attached to the academic environment, the improvement of organizational culture, and through it the development of the social capital of the university. The main task of work of SCA is to increase the educational competence of curators. As part of the implementation of this task, as the authors note, thanks to the use of training methods for advanced training, the exchange of teachers’ experience, and the creative atmosphere, the functions of relieving social tension in the team, elements of social therapy, establishing communication, and thus increasing the intellectual and social capital of teachers and organizations, were additionally performed., According to the survey, in which about 300 curators took part, more than 90% of teachers note the usefulness of the trainings. The SWOT-analysis of innovative experience was made. Key words: educational theory, curator, adviser, social capital, academic environment.